KRITIK ISRAR AHMAD KHAN TERHADAP HADIS-HADIS KITAB AL-QADAR DARI KITAB SAHIH AL-BUKHARI - Bin Kurdian, Nur Kholis; Abd. A’la; Muhammad Syarifudin (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2024)
To this day, matan ‘hadith text or context’ criticism remains an interesting discussion in hadith studies. One of the twenty-first century scholars who conducted matan criticism is Israr Ahmad Khan, a professor at Ankara University, Turkey. He criticised the hadith al-qadar ‘destiny’ from Sahih Bukhari. This article reveals Khan's method of matan criticism and his motivation for his criticism of these hadiths. This library research employs the content analysis technique. As a result, Khan's method of matan criticism focuses on the contradiction of the hadith with the findings of contemporary science, or with verses of the Qur'an, with other stronger hadiths, and with logic. In addition, Khan has a previous academic background as a theological scholar. As a result, the subject of Khan's research is theological hadiths related to al-qadar hadiths that are often debated by the theological schools of Jabariyah, Qadariyah, and Ahlussunnah wal Jama'ah.